1995
DOI: 10.1210/en.136.11.4732
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel parathyroid hormone (PTH) receptor with specificity for the carboxyl-terminal region of PTH-(1-84)

Abstract: Carboxyl-terminal fragments of PTH (C-PTH) appear to have biological properties different from those mediated by the amino-terminal portions of PTH and PTH-related peptide (PTHrP). To characterize a C-PTH receptor that may be involved in mediating these functions, we performed RRAs and affinity cross-linking studies with several clonal cell lines. Radiolabeled recombinant [Leu8,18,Tyr34]human PTH-(1-84)[mutPTH-(1-84) and [Tyr34] human PTH-(19-84)[mutPTH-(19-84) showed little or no specific binding to stably ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The results of radioreceptor binding assays in OC cells, using the 125 I-[Tyr 34 ]hPTH (19 -84) radioligand, were remarkably similar to those reported previously with ROS17/2.8 cells (6,16), which suggests that the CPTHRs on these different cell types probably are similar or identical. The results of radioreceptor binding assays in OC cells, using the 125 I-[Tyr 34 ]hPTH (19 -84) radioligand, were remarkably similar to those reported previously with ROS17/2.8 cells (6,16), which suggests that the CPTHRs on these different cell types probably are similar or identical.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The results of radioreceptor binding assays in OC cells, using the 125 I-[Tyr 34 ]hPTH (19 -84) radioligand, were remarkably similar to those reported previously with ROS17/2.8 cells (6,16), which suggests that the CPTHRs on these different cell types probably are similar or identical. The results of radioreceptor binding assays in OC cells, using the 125 I-[Tyr 34 ]hPTH (19 -84) radioligand, were remarkably similar to those reported previously with ROS17/2.8 cells (6,16), which suggests that the CPTHRs on these different cell types probably are similar or identical.…”
Section: Discussionsupporting
confidence: 85%
“…Enumeration of CPTHR sites on the OC cells led to estimates of 1,900,000 to 3,400,000 per cell, which was 6-to 10-fold higher than on the osteoblastic (F) cells obtained from the same bones and at least 5-fold higher than on ROS 17/2.8 cells (6). A survey of other available cell lines indicated that, with the exception of a bone marrow stromal cell line (MS-1) (25), little or no binding was detectable on NIH-3T3, HeLa or BHK21 fibroblast cells, as was reported previously for OK and LLC-PK1 kidney cells, YCC cells, and SaOS-2, MG63 and UMR106 -01 osteosarcoma cells (6).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The C-terminal region binds to another receptor (CPTHR), which responds exclusively to the C-terminal of PTH. [12] It has been shown that the C-terminal fragments may have discrete biological properties acting on the osteocyte to enhance its apoptosis,[13] accounting for the rationale for creating the N-terminal 1–34 PTH fraction.…”
Section: Teriparatidementioning
confidence: 99%